Targeting the DNA damage response and DNA repair pathways to enhance radiosensitivity in colorectal cancer - Deng, Siyao; Vlatkovic, Tijana; Li, Moying; Zhan, Tianzuo; Veldwijk, Marlon Romano; Herskind, Carsten (Cancers, 2022)
Radiotherapy is an important component of current treatment options for colorectal cancer (CRC). It is either applied as neoadjuvant radiotherapy to improve local disease control in rectal cancers or for the treatment of localized metastatic lesions of CRC. DNA double-strand breaks (DSBs) are the major critical lesions contributing to ionizing radiation (IR)-induced cell death. However, CRC stem cells promote radioresistance and tumor cell survival through activating cell-cycle checkpoints to trigger the DNA damage response (DDR) and DNA repair after exposure to IR. A promising strategy to overcome radioresistance is to target the DDR and DNA repair pathways with drugs that inhibit activated cell-cycle checkpoint proteins, thereby improving the sensitivity of CRC cells to radiotherapy. In this review, we focus on the preclinical studies and advances in clinical trials of DNA-dependent protein kinase catalytic subunit (DNA-PKcs), ataxia telangiectasia mutated (ATM), ataxia telangiectasia and Rad3-related kinase (ATR), checkpoint kinase 1 (CHK1), checkpoint kinase 2 (CHK2), WEE1 and poly (ADP-ribose) polymerase 1 (PARP1) kinase inhibitors in CRC. Importantly, we also discuss the selective radiosensitization of CRC cells provided by synthetic lethality of these inhibitors and the potential for widening the therapeutic window by targeting the DDR and DNA repair pathways in combination with radiotherapy and immunotherapy.